The administration and management in economics development of waqf land - Mokhtar, Salbiah (2008)
Waqf is an Islamic concept of trust when an owner donates a land or property for a specific or general welfare of Muslim community. Basically waqf land is capable to contribute in economy and social benefits for the Muslims society. Currently Malaysia posses about 9,907 hectares of waqf land but the majority use of these assets are limited for mosque, cemetery, surau and orphanage. This has hindered waqf property from generating income that can benefit the Muslim society in this country. Although economic activities are not the main purpose of waqf but undoubtedly the profits gain will generate more charitable activities for the ummah. Waqf land is still subjected to several problems, among others are the abandonment and unutilised of land due to physical factors, legal aspects, inefficient databases and the most important issue is the management and administration of the State Islamic Religious Councils (SIRCs) as the sole trustee of waqf assets. Land as scarce resources should not be abandoned or unutilised. This will be a waste to economic of the area. As urban planners land is treated as prominent assets which need to be well managed and develop. Hence, land matter related to waqf needs to be understand, so constructive suggestion could be offered to improve the land management. Supposedly, to improve the economic development of waqf should commence from the administration strategy. Scenario in Malaysia shows that there is no uniformity of jurisdiction between SIRCs and certain SIRCs is adapting more contemporary ijtihadi (rule base on fatwa) in waqf administration and management. Thus this paper will explore and examine related aspects to understand the role of the trustees. Finally, this paper is hope to disclose methods adapted by SIRCs in their administrations and to what extent that the SIRCs struggle to establish the waqf up to its best use economically and socially without compromising its philanthropic duty.